ANALISIS INFORMASI CITRA SEKUENS SAGITAL T2 PROPELLER MRI CERVICAL KLINIS HERNIA NUKLEUS PULPOSUS (HNP) PADA PASIEN TIDAK KOOPERATIF - Simon Nuari (Jurnal Imejing Diagnostik (JImeD), 2026)
Research Background: Magnetic Resonance Imaging (MRI) is a non-invasive imaging modality that does not involve ionizing radiation and is highly effective in evaluating the soft tissue abnormalities, including those of the cervical vertebrae. In this matter, one of the most frequently encountered disorders in this region is cervical herniated nucleus pulposus (HNP), which may cause neck pain and radiculopathy and consequently reduce the patients’ quality of life. MRI is the primary imaging modality for establishing the diagnosis of HNP because it can clearly visualize among the other things the intervertebral discs, spinal cord, and intervertebral foramina. In clinical practice, however, cervical MRI examinations often encounter the motion artifacts, particularly in the patients with psychiatric disorders who tend to be uncooperative. In relation to which, T2 PROPELLER (Periodically Rotated Overlapping Parallel Lines with Enhanced Reconstruction) technique is known to be able to reduce the motion artifacts, thereby improving image quality and diagnostic value compared to the conventional T2-weighted sequences. Research Objective: This research aims to analyse the examination procedure and the quality of anatomical image information obtained from sagittal T2 Propeller sequences in cervical MRI for the cases of herniated nucleus pulposus (HNP) in the uncooperative patients with psychiatric disorders at RSKD Duren Sawit. Research Design: This research constitutes a qualitative study which was undertaken at Radiology Department of Duren Sawit Regional Special Hospital starting from August up to November 2025. The research employed an analytical approach to cervical MRI examinations using an additional sagittal T2 Propeller sequence in clinically diagnosed cases of herniated nucleus pulposus (HNP) in the uncooperative patients. As for the sample, it consisted of three patients selected based on the predefined inclusion and the exclusion criteria. While primary data were then obtained from direct observation of the MRI examination procedures and image acquisition results. Research Results: Based on the findings of this research conducted at Duren Sawit Regional Special Hospital, it can be concluded that the cervical MRI examination procedure for clinically diagnosed cases of herniated nucleus pulposus (HNP) in the uncooperative patients with psychiatric disorders was performed in accordance with the established theoretical principles, with the addition of sagittal oblique and sagittal T2 PROPELLER sequences. The sagittal T2 Propeller sequence was shown to produce greater image quality compared to the routine T2-weighted sequences, as it can effectively reduce the motion artifacts and enhanced the visualization of the spinal cord, intervertebral discs, and vertebral bodies.